2022
DOI: 10.1017/s0954579422000396
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of mental health during a year of the COVID-19 pandemic

Abstract: Belonging is a basic human need, with social isolation signaling a threat to biological fitness. Sensitivity to ostracism varies across individuals and the lifespan, peaking in adolescence. Government-imposed restrictions upon social interactions during COVID-19 may therefore be particularly detrimental to young people and those most sensitive to ostracism. Participants (N = 2367; 89.95% female, 11–100 years) from three countries with differing levels of government restrictions (Australia, UK, and USA) were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…The following measures were included in the present study. The full list of measures included in the CORAL study at T1 has been reported by Minihan et al 12…”
Section: Methodsmentioning
confidence: 99%
“…The following measures were included in the present study. The full list of measures included in the CORAL study at T1 has been reported by Minihan et al 12…”
Section: Methodsmentioning
confidence: 99%
“…Only the measures relevant to the present study are described below (for the full list of measures see 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…A further source of stress introduced by the pandemic, beyond health and economic uncertainty, are social distancing measures implemented to reduce the spread of COVID-19 18 . These measures have limited access to, and social contact with healthcare providers, as well as social support from relatives and friends for all 19 and may have been particularly detrimental to the wellbeing of pregnant women.…”
Section: Social Vulnerability To Covid-19-related Stressmentioning
confidence: 99%
See 2 more Smart Citations